Canopy height‐to‐row spacing ratio as a simple and practical onsite index to determine the time for terminating Ipomoea coccinea control in the Japanese soybean‐growing systems. Issue 3 (7th July 2015) - Kurokawa, Shunji; Hajika, Makita; Shibuya, Tomoko
<x xml:space="preserve">Abstract</x> In order to determine the time for terminating Ipomoea coccinea control in Japanese soybean‐growing systems, the relationship between the relative photosynthetic photon flux density at the emergence time of I. coccinea seedlings and their fate in competition with a Japanese determinate soybean cultivar, "Hatayutaka", was investigated. A 2 year field study was conducted, in which I. coccinea was seeded at 0, 5 and 7 weeks after seeding of the soybean in 2010 and once per week between 0 and 7 weeks after seeding in 2011, while soybean was seeded in six plots at three different seeding times and two different row‐spacing arrangements with the same intrarow spacing. The results showed that the I. coccinea seedlings that emerged at a relative photosynthetic photon flux density of <49% grew weak or died. At this value, the canopy height‐to‐row spacing ratio of soybean was very stable, regardless of the row spacing, in both study years. This ratio was also stable when tested on 11 different soybean cultivars that covered all cultivation areas of Japan and had various growth speeds during the early growing period. A canopy height‐to‐row spacing ratio of 1.0 could be a simple and practical onsite index for determining the time to terminate I. coccinea control in Japanese soybean‐growing systems.